The occurrence of residual curarisation in postoperative patients at an academic hospital - Hassim, Sakeena (My University, 2016)
Postoperative residual curarisation (PORC) resulting from the use of non depolarising muscle relaxants continues to be a significant problem. It is associated with an increase in morbidity and may delay discharge from the recovery room, increasing financial costs. An objective measurement of neuromuscular functioning using an accelerometer is recommended to ensure patient safety. The aim of this study was to describe the occurrence of PORC in the recovery room in patients who have received intermediate acting NDMRs intraoperatively at CHBAH. This was a prospective, contextual and descriptive study. The study sample included ASA 1 to 3 adult patients who had received an intermediate acting NDMR during elective surgery and had given pre operative consent to participate in the study. Neuromuscular function was monitored using acceleromyography. A TOF ratio < 0.9 was defined as having PORC. Data collection took place during December 2014 to February 2015. Data was analysed using descriptive and inferential statistics. The study sample consisted of 55 patients. Twenty five patients had a TOF ratio < 0.9 on arrival in the recovery room. The occurrence of PORC was therefore 45.46%. Intraoperative neuromuscular monitoring was documented to have been done in 3 (5.45%) of the patients. The most frequently used NDMRs were rocuronium 31 (56.36%) and cisatracurium 9 (16.36%). There was no statistically significant differences in the occurrence of PORC relating to the NDMR used (p=0.72) but higher percentages were observed with cisatracurium 5 (55.56%). An anticholinesterase as reversal agent was used in 48 (87.27%) of the patients. PORC was significantly more frequent in patients who did not receive an anticholinesterase (85.71 vs. 39.58%, p=0.03). Three patients presented with a temperature < 35 °C. Incomplete neuromuscular recovery was more frequent in patients with a temperature < 35 °C, 2 (66.67%) compared to the patients with a temperature ≥ 35 °C 23 (44.23%) PORC remains a clinical problem in the recovery room. To ensure patient safety objective neuromuscular monitoring needs to be performed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology, Johannesburg, 2016